2020
DOI: 10.31234/osf.io/su3nv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 pandemic on pregnant women in Bosnia and Herzegovina and Serbia

Abstract: This study investigated the psychological impact of the COVID-19 pandemic in pregnant women from Bosnia and Herzegovina and Serbia during March and April 2020. 152 respondents filled out an online administered questionnaire assessing psychological impact of the COVID-19 pandemic, fear of COVID-19 infection and death, attachment styles, perceived social support and other relevant sociodemographic and life history variables. The results indicate that the COVID-19 pandemic significantly impacts the level of fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Of the total 29 studies, 10 were excluded due to inconsistency of results. 31 40 Eventually, 19 eligible studies were used in the final analysis of the current systematic review and meta-analysis 41 59 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the total 29 studies, 10 were excluded due to inconsistency of results. 31 40 Eventually, 19 eligible studies were used in the final analysis of the current systematic review and meta-analysis 41 59 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of total of 19 studies included in the final analysis, four studies were done in Canada, 42 , 47 , 52 , 57 three studies in China, 48 , 50 , 56 two in Iran, 41 , 45 six in European countries (Belgium, 55 United Kingdom, 44 Turkey, 58 Ireland, 51 Bosnia and Herzegovina and Serbia, 46 and Italy 49 ), and the rest were conducted in the United States, 59 Colombia, 53 and Sri Lanka. 54 All studies were cross-sectional studies and critical appraisal of cross-sectional studies conducted revealed that about 95% of studies scored more than 75%, only one scored lowest scored 62.5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study in Italy found that the COVID-19 outbreak caused a moderate psychological impact on pregnant women, and around 53% of respondents reported severe psychological impact [ 22 ]. A study done in Bosnia and Herzegovina and Serbia reported that around that 34.2% of respondents experienced a severe psychological impact, 9.9% experienced moderate, and 23.0% of respondents had mild psychological impact due to the COVID-19 outbreak [ 23 ]. Another study done in China showed that the mean IES score of pregnant women was higher than the present study, with 67.1% of pregnant women had an IES ⩾26, indicating moderate-to-severe psychological impact during the outbreak of the COVID-19 pandemic [ 24 ].…”
Section: Discussionmentioning
confidence: 99%